2020
DOI: 10.1049/el.2020.0283
|View full text |Cite
|
Sign up to set email alerts
|

Spiking neural network approaches PCA with metaheuristics

Abstract: This Letter presents meaningful results that demonstrate the reduction of dimensionality by spiking neural networks (SNNs) on benchmarking data. This experimental scheme includes metaheuristics, namely, the artificial bee colony algorithm (ABC algorithm) for finding optimal conductance values in the SNNs. Therefore, the objective function in the used ABC algorithm leads the SNNs to compute the principal component analysis (PCA), efficiently. The eigendecomposition of the information drawn by the SNNs in the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…VECTOR and ETAS Electrobit have AUTOSAR solutions. Currently, ECU-related security technologies include secure boot, secure flash, and secure access control, which are used not only as ECU protection but also as element technologies for safe remote updates such as SOTA/FOTA (Software-over-the-air/Firmware-over-the-air) [22][23][24][25].…”
Section: Automobile Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…VECTOR and ETAS Electrobit have AUTOSAR solutions. Currently, ECU-related security technologies include secure boot, secure flash, and secure access control, which are used not only as ECU protection but also as element technologies for safe remote updates such as SOTA/FOTA (Software-over-the-air/Firmware-over-the-air) [22][23][24][25].…”
Section: Automobile Securitymentioning
confidence: 99%
“…not only as ECU protection but also as element technologies for safe remote updates such as SOTA/FOTA (Software-over-the-air/Firmware-over-the-air) [22][23][24][25].…”
Section: Automobile Securitymentioning
confidence: 99%
“…On the other hand, training spiking systems based on metaheuristics could be divided into two branches, firing rate and spike-time delay. The works in [6][7][8] belong to the first category meanwhile those cited in [9][10][11] to the second one. The cuckoo search algorithm in [6], which uses a random walk strategy, achieves the spiking training phase on six complex databases.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the ABC algorithm improves the quality of the results compared with earlier metaheuristic methods. The work in [8] trains with the ABC algorithm a one-layer spiking neural network to reduce the dimension of complex datasets into 3D spaces in a linear way. In improving the training of spiking systems, similar researchers are found in [9,10] a decade apart.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation